Pemikiran Pendidikan Imam Al Ghazali dalam Kitab Ihya’ Ulumiddin - ERFAN HABIBI; Dyah Nawangsari; Hepni Zain; Ubaidillah Ubaidillah; Musyaffa Rafiqie (Program Studi Pendidikan Agama Islam STAI Sayid Mohammad Alawi Al Maliki, 2025)
This paper examines Imam Al-Ghazali's educational thought and its relevance in the modern world of education. As a great scholar in the Islamic tradition, Al-Ghazali emphasized that education is not only for the transfer of knowledge, but also for the formation of individual character and spirituality. Through a library research approach, this study explores Al-Ghazali's ideas on moral and moral education, and assesses whether his views are still relevant to address contemporary educational challenges. Al-Ghazali proposed active, reflective and spiritual values-oriented learning methods, which can be adapted to strengthen moral and ethical education in the modern era. This research aims to bridge traditional thought and today's educational needs, while identifying the positive contributions that Al-Ghazali's thought can make to the modern education system.